DETERMINAN HARGA SAHAM PADA PERUSAHAAN PERBANKAN: PERAN KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL, DAN PROFITABILITAS - Retno Indah Kusuma Dewi; Desy Nur Pratiwi; Yuwita Ariessa Pravasanti (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the influence of independent commissioners, institutional ownership, and profitability on stock prices in banking companies listed on the Indonesia Stock Exchange for the 2022–2025 period. This study uses a quantitative approach with secondary data obtained from company annual reports and stock price data. The research sample was determined using a purposive sampling method. Data analysis was performed using multiple linear regression using SPSS version 27 software, which includes descriptive statistical analysis, classical assumption tests, coefficient of determination tests, F tests, and t tests. The results show that, partially, independent commissioners have a negative and significant effect on stock prices, while institutional ownership and profitability have a positive and significant effect on stock prices. Simultaneously, independent commissioners, institutional ownership, and profitability have a significant effect on stock prices in banking companies listed on the Indonesia Stock Exchange.